Sustainability Issues in Social Model of Coporate Social Responsibility Theoretical Analysis and Practical Implication - THAO, Vo Thi Thu; TIEN, Nguyen Hoang; ANH, Dinh Ba Hung (Journal of Advanced Research in Management, 2019)
This article delivers a full insight into social model of corporate social responsibility (CSR) based on stakeholders’ theory and wider concept of corporate sustainability. The social model of CSR is oriented towards corporate sustainability issues including sustainable performance and development of enterprise with super goal that is searching for a strategic equilibrium between financial performance, social development and environmental sustainability. The article will point out the importance and relevance of social model of CSR as it is suitable for enterprises in today’s global business and indicate its implementation as corporate top priority. The article also presents challenges in implementation of social model of CSR in enterprises of developing countries, following steps that enterprises of developed countries have been through. Using extensive theoretical analysis and in-depth empirical synthesis of previous researches’ findings as selected methodology of study, the article investigates sustainably viable solutions and recommendations to enhance social responsibility and sustainability awareness and business practices in contemporary business and economy.